Posttransplantation cyclophosphamide improves transplantation outcomes in patients with AML/MDS who are treated with checkpoint inhibitors. Issue 10 (3rd March 2020) - Oran, Betül; Garcia‐Manero, Guillermo; Saliba, Rima M.; Alfayez, Mansour; Al‐Atrash, Gheath; Ciurea, Stefan O.; Jabbour, Elias J.; Mehta, Rohtesh S.; Popat, Uday R.; Ravandi, Farhad; Alousi, Amin M.; Kadia, Tapan M.; et al.
Abstract : Background: There have been concerns regarding increased peritransplantation complications, especially severe acute graft‐versus‐host disease (aGVHD), in patients with prior use of checkpoint inhibitors (CPI) before hematopoietic stem cell transplantation (HSCT). Methods: The authors performed a retrospective study of 43 patients with acute myeloid leukemia and/or myelodysplastic syndromes who were treated with an antiprogrammed cell death protein 1 (PD‐1) (32 patients) or anticytotoxic T‐lymphocyte–associated protein 4 (CTLA‐4) (9 patients) blockade or both (2 patients) prior to HSCT with the primary outcome of aGVHD by day 100 after HSCT. Outcome analyses were stratified by GVHD prophylaxis as use of post‐HSCT cyclophosphamide (PTCy) (22 patients) or not (non‐PTCy) (21 patients). Results: The PTCy group demonstrated a trend toward lower grade 3 to 4 aGVHD when compared with the non‐PTCy group (5% vs 22%), although the rates of grade 2 to 4 aGVHD were comparable (49% vs 56%). The interval between CPI and HSCT did not appear to impact the incidence of aGVHD. However, a higher incidence of grade 3 to 4 aGVHD was observed in patients who received >4 treatments of CPI prior to HSCT if they were not given PTCy as GVHD prophylaxis (43% vs 12%). Matched control analyses using patients with no prior use of CPI confirmed the increase in grade 3 to 4 aGVHD with those agents. However, that increased risk was limited to patients who did not receive PTCy and was not observed in patients who received PTCy as GVHD prophylaxis. Despite persistent improvement in GVHD with the use of PTCy, disease control was not compromised and progression‐free survival at 1 year was found to be superior for patients treated with PTCy compared with those not receiving PTCy among patients with prior use of CPI (55% vs 22%). Conclusions: The results of the current study indicated that HSCT with prior use of CPI appears feasible in patients with acute myeloid leukemia and/or myelodysplastic syndromes and the use of PTCy as GVHD prophylaxis improves outcomes. Abstract : The use of checkpoint inhibitors (CPI) prior to hematopoietic stem cell transplantation (HSCT) in patients with acute myeloid leukemia and/or myelodysplastic syndromes affects transplantation outcomes, with an especially increased incidence of grade 3 to 4 acute graft‐versus‐host disease (aGVHD). The use of post‐HSCT cyclophosphamide as GVHD prophylaxis in patients treated with CPI prior to transplantation is found to lead to improved transplantation outcomes, including grade 3 to 4 aGVHD.